2016
DOI: 10.7554/elife.15441
|View full text |Cite
|
Sign up to set email alerts
|

Persistent neural activity in auditory cortex is related to auditory working memory in humans and nonhuman primates

Abstract: Working memory is the cognitive capacity of short-term storage of information for goal-directed behaviors. Where and how this capacity is implemented in the brain are unresolved questions. We show that auditory cortex stores information by persistent changes of neural activity. We separated activity related to working memory from activity related to other mental processes by having humans and monkeys perform different tasks with varying working memory demands on the same sound sequences. Working memory was ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 70 publications
5
48
0
Order By: Relevance
“…Sustained maintenance activation has now been observed across multiple brain regions in tasks involving various sensory modalities (Bashivan et al, 2014a;Masse et al, 2020;Salazar et al, 2012; but see Yue et al, 2019). In agreement with prior neuroimaging studies on WM (Grimault et al, 2014;Huang et al, 2016;Vogel and Machizawa, 2004), we similarly find that sustained EEG activity during WM maintenance is modulated by stimulus load. Our results corroborate fMRI findings (Kumar et al, 2016) by confirming, electrophysiologically, that successful auditory WM depends on elevated activity within AC and adjacent auditory cortex.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Sustained maintenance activation has now been observed across multiple brain regions in tasks involving various sensory modalities (Bashivan et al, 2014a;Masse et al, 2020;Salazar et al, 2012; but see Yue et al, 2019). In agreement with prior neuroimaging studies on WM (Grimault et al, 2014;Huang et al, 2016;Vogel and Machizawa, 2004), we similarly find that sustained EEG activity during WM maintenance is modulated by stimulus load. Our results corroborate fMRI findings (Kumar et al, 2016) by confirming, electrophysiologically, that successful auditory WM depends on elevated activity within AC and adjacent auditory cortex.…”
Section: Discussionsupporting
confidence: 89%
“…Some reports show enhancements (Gaab et al, 2003a;Grimault et al, 2009;Kumar et al, 2016) and others suppression (Linke et al, 2011;Zatorre et al, 1994) of auditory cortical responses with memory load. ERP studies are similarly ambiguous with studies showing a decrease (Golob and Starr, 2000;Pratt et al, 1989) or increase (Alain et al, 2009;Grimault et al, 2014;Huang et al, 2016;Lefebvre et al, 2013;Vogel and Machizawa, 2004) in late (> 400 ms) slow wave potentials with load level. On the contrary, direct unit recordings from animals suggest AC neurons can actually show both suppression and enhancement effects according to the mnemonic context of sounds (Scott et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that delay activity in the auditory cortex reflects the content of auditory WM (Huang et al, 2016;Kumar et al, 2016;Uluç et al, 2018). Thus, similar to visual WM maintenance, which has been found to result in content-specific delay-activity in the visual cortex (Harrison & Tong, 2009), auditory WM content is also maintained in a network that recruits the same brain area responsible for sensory processing.…”
Section: Discussionmentioning
confidence: 89%
“…Previous research has relied on testing whether sensory cortices exhibit content-specific neural activity during maintenance. While this has indeed been shown for visual memories in occipital areas (e.g., Harrison & Tong, 2009) and, more recently, for auditory memories in the auditory cortex (Huang, Matysiak, Heil, König, & Brosch, 2016;Kumar et al, 2016;Uluç, Schmidt, Wu, & Blankenburg, 2018), WM-specific activity in the sensory cortex is not always present (Bettencourt & Xu, 2016), fuelling an ongoing debate over whether sensory cortices are necessary for WM maintenance (Scimeca, Kiyonaga, & D'Esposito, 2018;Xu, 2017). However, the neural WM network may not be solely based on measurable neural activity, and it has been proposed that information in WM may be maintained in an "activity-silent" network (Stokes, 2015) -for example, changes in short-term connectivity (Mongillo, Barak, & Tsodyks, 2008).…”
Section: Introductionmentioning
confidence: 78%